Optimal Sizing and Location of Multi-Unit Photovoltaic System on Distribution Network Using Particle Swarm Optimization - Mohd Najib , Mohamad Nor Akhmal; Abdullah, Mohd Noor; Wagiman, Khairul Rijal; Junus, Mochammad (Journal of Electronic Voltage and Application, 2025)
This paper investigates the optimal sizing and location of multi-unit photovoltaic (PV) systems in a distribution network using Particle Swarm Optimization (PSO). The goal is to reduce power losses and improve voltage stability by installation PV as distributed generator (DG). The IEEE 33-bus and 69-bus radial distribution systems were used as test system. Power flow analysis was conducted using the Newton-Raphson method in MATLAB software. Simulation results revealed that integrating three PV units provided the best performance, reducing power losses by 65.52% and 69.16% for the IEEE 33-bus and 69-bus systems respectively. A scenario with a 20% increase in total load was also analyzed to simulate the impact of electric vehicle charging station (EVCS) to PV sizing and location. It found that, proper sizing and placement of PV integration can improve the network losses when EVCS connected to the distribution system.